Transfer Pricing Transaction: Solution Or Fraud - et. al., Suryana, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to analyze whether this transfer pricing transaction is a solution for companies or a tool to commit fraud or avoid taxes imposed by the government on companies. This study also tested the effect of the variable tax expense on transfer pricing and the effect of the bonus mechanism on transfer pricing. The research method used is descriptive research method and verification with a quantitative approach. The sample used in analyzing the effect of tax expense and bonus mechanisms on transfer pricing was 13 coal sub-sector companies listed on the Indonesia Stock Exchange (IDX) with the period 2016-2018.The results showed that the tax expense and the bonus mechanism affected transfer pricing either partially or simultaneously. Thus, the subsidiary and the parent company can conduct transactions that can be regulated, just like the company suffered a loss in one country to reduce the tax expense in Indonesia. Multinational companies tend to shift their tax liabilities from countries with high rates to countries with lower tax rates by reducing the selling price between companies within a group. And companies have the potential to manipulate financial statements to maximize profits. The greater the overall company profit generated, the better the image of the directors in the eyes of the company owner. Therefore, the board of directors can do everything possible to maximize company profits, including transfer pricing practices.Thus transfer pricing transactions can be a solution for multinational companies but can also be a tool to commit fraud in making financial reports, especially concerning tax obligations.